Physiological Aspects of Cauliflower Plants Affected by Fertigation Intervals and Doses of Various Inter - Season Soil Ameliorants in Coastal Sandy Land - Junaedi, Mahbub; Saparso, Saparso; Rif'an, Muhamamad (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2018)
Cauliflower is one of vegetable commodities mostly consumed. The study aimed to determine fertigation interval and application of soil ameliorants including the types, doses, and frequency that are appropriate for the growth and productivity of cauliflower plants in coastal sandy land. The research was carried out in the sandy beach area of Jetis, Banjarsari Village, Nusawungu District, Cilacap Regency from April 2017 to September 2017. The study was arranged in Randomized Complete Block Design (RCBD) factorial split plot. Data were analyzed by ANOVA followed by DMRT at 5 %. The results showed that (1) the fertigation interval did not significantly affect the growth, yield and physiology variables of cauliflower plants; (2) the frequency of soil ameliorants application had significant effect on the variable growth and yield of cauliflower plants. The application of soil ameliorants every season gave the best results compared to application every two seasons; (3) the application of soil ameliorants of Vertisol soil and manure could increase growth and yield variables compared but did not affect the physiology of cauliflower plants.